Systematic literature review of observational cohorts and clinical trials into the success rate of glucocorticoid discontinuation after their use as bridging therapy in patients with rheumatoid arthritis. Issue 7 (25th April 2022) - van Ouwerkerk, Lotte; Palmowski, Andriko; Nevins, Isabell S; Buttgereit, Frank; Verschueren, Patrick; Smolen, Josef S; Landewé, Robert BM; Bijlsma, Johannes JW; Kerschbaumer, Andreas; Westhovens, René; Huizinga, Tom WJ; Allaart, Cornelia F; et al.
Abstract : Objective: To investigate the success rate of glucocorticoid (GC) discontinuation during follow-up in observational cohorts and clinical trials using temporary GC as part of initial therapy ('bridging') in newly diagnosed patients with rheumatoid arthritis (RA). Methods: Systematic literature searches were conducted to identify observational cohorts and clinical trials including patients with RA treated with initial GC bridging therapy, defined as discontinuation of GC within 1 year. Patient percentages still using GC were considered the reverse of successful discontinuation. Random effects meta-analyses were performed stratified by time point. Results: The scoping literature search for observational cohort studies could not identify studies answering the research question. The literature search for clinical trials identified 7160 abstracts, resulting in 10 included studies, with varying type and dose of GC and varying tapering schedules, of which 4 reported sufficient data on GC discontinuation or use after the bridging phase. The pooled proportion of patients who were still or again using GC was 22% (95% CI 8% to 37%, based on four trials) at 12 months and 10% at 24 months (95% CI −1 to 22, based on two trials). Heterogeneity was substantial (I²≥65%). Conclusion: The success rate of GC discontinuation after bridging as part of initial treatment of RA has been described in a limited number of studies. Reports on observational cohorts did not answer the research question. In clinical trials, protocolised discontinuation was mostly successful, although 22% of the patients who started GC bridging therapy still or again used GC at 12 months, and 10% at 24 months.